Enantiomerically enriched tetrahydropyridine allyl chlorides - Karabiyikoglu, S; Brethome, AV; Palacin, T; Paton, RS; Fletcher, SP (Royal Society of Chemistry, 2020)
Enantiomerically enriched allyl halides are rare due to their configurational lability. Here we report stable piperidine-based allyl chloride enantiomers. These allyl chlorides can be produced via kinetic resolution, and undergo highly enantiospecific catalyst-free substitution reactions with C, N, O and S-based nucleophiles. DFT calculations and experiments with deuterium-labelled chloro-tetrahydropyridine, selectively prepared using H/D primary kinetic isotope effect, were used to investigate the mechanisms of resolution and substitution reactions. The allyl chlorides may also serve as valuable mechanistic tools for probing stereoselective reaction pathways.